Field‐oriented control based on hysteresis band current controller for a permanent magnet synchronous motor driven by a direct matrix converter. Issue 7 (3rd May 2018) - Zhang, Jianwei; Yang, Haitao; Wang, Tianshi; Li, Li; Dorrell, David G.; Lu, Dylan Dah‐Chuan
Abstract : The hysteresis band controller offers excellent dynamic performance. It has been widely researched and applied to the voltage source inverter and inverter fed drives, however it has not been investigated within the context of a matrix converter or a matrix converter based motor drive. In this study, both fixed‐band and sinusoidal‐band hysteresis current controllers are proposed and developed for a direct matrix converter. A comprehensive comparative evaluation of the two methods is then carried out. Both methods have fast dynamic performance and they inherently integrate the line modulation technique of the virtual rectifier stage into the overall modulation. Surge currents are prevented with the proposed scheme. The sinusoidal‐band hysteresis controller demonstrates lower total harmonic distortion at the expense of higher average switching frequency, which is only significantly observable at very high sampling frequencies. The proposed controller is integrated with the field‐oriented control to drive a matrix converter fed permanent magnet synchronous machine. The proposed methods are simple and incur a light computational burden, which advances the practical applications of matrix converters in AC motor drives. The simulation and experiment results demonstrate the effectiveness and feasibility of the proposed scheme.